2022
DOI: 10.3390/biomedicines10071526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Humoral Immune Response Following COVID-19 Vaccination in Healthcare Workers: A One Year Longitudinal Study

Abstract: The continuous variability of SARS-CoV-2 and the rapid waning of specific antibodies threatens the efficacy of COVID-19 vaccines. We aimed to evaluate antibody kinetics one year after SARS-CoV-2 vaccination with an mRNA vaccine in healthcare workers (HCW), with or without a booster. A marked decline in anti-Spike(S)/Receptor Binding Domain (RBD) antibody levels was registered during the first eight months post-vaccination, followed by a transitory increase after the booster. At three months post-booster an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Our data strengthen previous findings demonstrating that immunization to SARS-CoV2 through vaccination induces a peak in antibody response soon after vaccination, followed by a marked and progressive decline of anti-Spike IgG antibodies during a 9 months period after vaccination (Levin et al, 2021;Chivu-Economescu et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data strengthen previous findings demonstrating that immunization to SARS-CoV2 through vaccination induces a peak in antibody response soon after vaccination, followed by a marked and progressive decline of anti-Spike IgG antibodies during a 9 months period after vaccination (Levin et al, 2021;Chivu-Economescu et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The booster dose induced a transitory increase in humoral response, restoring antibody levels to the initial values yielded by primary vaccination (Chivu-Economescu et al, 2022;Desmecht et al, 2022), particularly in naïve individuals (never infected). Even more, heterologous vaccination (primary vaccination with Comirnaty vaccine followed by Spikevax booster) elicited higher anti-SARS-CoV2 antibodies response with respect to homologous (Comirnaty/ Comirnaty) vaccination regimens, confirming literature data (Naito et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…Of note, as much as 82% of the participants decided to receive a booster shot of the Comirnaty vaccine. A similar percentage (70%) has been reported by Chivu-Economescu et al [ 25 ], which proves a high level of confidence in the immunity conferred by the COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Lee et al have also reported a higher level of anti-S antibodies 4 months after booster in subjects infected with SARS-CoV-2 within this period in comparison to the boosted participants without SARS-CoV-2 infection. The phenomenon named hybrid immunity—stemming from combined vaccination and infection, has been linked to a higher protection against SARS-CoV-2 and its variants, and explained by the induction of more broadly neutralizing antibodies and a stronger cellular immune response [ 25 , 29 , 30 ]. Lee at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation